Hand Sanitizer Gel Formulation with Laccase Enzyme as an Antibacterial Against Staphylococcus aureus and Escherichia coli - Sita Heris Anita; Asishe Asishe; Vilya Syafriana; Amelia Febriani; Deni Zulfiana; Maulida Oktaviani; Oktan Dwi Nurhayat; Dede Heri Yuli Yanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Laccase enzymes have been used widely in industrial fields such as textile, pulp, paper, food, cosmetic, and pharmaceutical industries. Laccase is used in toothpaste, mouthwash, deodorants, and soaps in personal care products. Previously, laccase enzymes had never been used for formulating hand sanitizer gel. This study aimed to determine the effect of the laccase enzyme on the physicochemical properties and the antibacterial potential of the hand sanitizer gel against pathogenic bacteria. Laccase enzyme was produced through fermentation using the fungus Trametes hirsuta EDN 082 with an activity of 0.032 U/mL. Hand sanitizer gel was made with the addition of laccase enzyme with varying concentrations of 4, 7, and 10% (v/v). The physicochemical test included organoleptic tests, pH evaluation, gel spreadability, and viscosity. The antibacterial was tested by the palm swab method. The gel physicochemical characteristics showed that the more laccase enzyme added, the more yellow the color produced, the less thick the shape, the wider the gel spreadability, and the lower the viscosity. The obtained pH ranged from 7.4 to 7.6. The best formulation of the hand sanitizer gel was achieved with the addition of a 7% (v/v) laccase enzyme. This formulation can reduce the number of bacteria colonies of Staphylococcus aureus and Escherichia coli on the palms with effectiveness above 95%. The laccase enzyme can be used as an active ingredient and antibacterial agent in the formulation of hand sanitizers.